2022
DOI: 10.3390/educsci12040247
|View full text |Cite
|
Sign up to set email alerts
|

Student Approaches and Performance in Element Sequencing Tasks Using 2D and Augmented Reality Formats

Abstract: In civil and construction engineering education research, a focus has been on using 3D models to support students’ design comprehension. Despite this trend, the predominant mode of design communication in the industry relies on 2D plans and specifications, which typically supersede other modes of communication. Rather than focusing on the presentation of less common 3D content as an input to support students’ understanding of a design, this paper explores more common 2D inputs, but compares different visualiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…On the other hand, applications are able to deliver visualisations of nonexistent buildings and new projects in existing environments where a project is located. They are also able to deliver more awareness of the relationship of the components of the structure and the phases of the work through the four-dimensional (4D) BIM model, providing a better understanding of the spatial movement of equipment, materials, and placement of components in the work, resulting in a more optimised design for the operation phase [47,51,62,63,81,86,94,101,107]. For structural analysis, the applications provide visualisation capabilities for structural buckling according to the mode of vibration, knowledge and spatial visualisation skills, and visualisation of deformations, support reactions, load transfer between elements, and internal forces in different types of structures for different types and load combinations [33,93].…”
Section: A1-structural Areamentioning
confidence: 99%
“…On the other hand, applications are able to deliver visualisations of nonexistent buildings and new projects in existing environments where a project is located. They are also able to deliver more awareness of the relationship of the components of the structure and the phases of the work through the four-dimensional (4D) BIM model, providing a better understanding of the spatial movement of equipment, materials, and placement of components in the work, resulting in a more optimised design for the operation phase [47,51,62,63,81,86,94,101,107]. For structural analysis, the applications provide visualisation capabilities for structural buckling according to the mode of vibration, knowledge and spatial visualisation skills, and visualisation of deformations, support reactions, load transfer between elements, and internal forces in different types of structures for different types and load combinations [33,93].…”
Section: A1-structural Areamentioning
confidence: 99%
“…The task the students were given were aimed at resembling a typical carpentry task that one might encounter on a construction site, and the results showed that even though the students who had to use 2D design finished faster than their peers, their design was more prone to errors and did not meet the required dimensional details. In contrast, their AR colleagues had fewer errors and saw the exercise as an opportunity to develop hands-on skills [26].…”
Section: Ar In Engineeringmentioning
confidence: 97%
“…In civil and construction engineering, AR was used to examine how students could use design plans to understand the sequence of constructing a wall in a typical residential building. This experiment had two groups of students, where the first group recorded their results on a 2D worksheet the other group used AR [26]. The task the students were given were aimed at resembling a typical carpentry task that one might encounter on a construction site, and the results showed that even though the students who had to use 2D design finished faster than their peers, their design was more prone to errors and did not meet the required dimensional details.…”
Section: Ar In Engineeringmentioning
confidence: 99%